Fresh herbage for dairy cattle : the key to sustainable food chain - Dijkstra, J. [ (Jan)] , 1964-; Elgersma, Anjo; Tamminga, Seerp (Wageningen UR frontis series, 2006)
Offers contributions of active researchers and leading experts in the field of grassland management and grass utilization. This book follows the food chain, moving from the big picture to basic principles of grassland management and effects on herbage quality, intake and nutrient flows